2005
DOI: 10.1111/j.1479-828x.2005.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Misoprostol for second and third trimester termination of pregnancy: A review of practice at the Women's and Children's Hospital, Adelaide, Australia

Abstract: Side-effects increase with increasing dose of misoprostol. Induction following intrauterine fetal death is associated with a need for lower doses of misoprostol and a shorter induction to birth interval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…As multiparous women and women with shorter gestation were more likely to complete the termination faster, they required less prostaglandin. This trend of decreased need of prostaglandin in multiparous women has also been recognized by Dodd et al (30); lower gestational age may also function as a predictor of shorter induction-to-abortion time (11).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…As multiparous women and women with shorter gestation were more likely to complete the termination faster, they required less prostaglandin. This trend of decreased need of prostaglandin in multiparous women has also been recognized by Dodd et al (30); lower gestational age may also function as a predictor of shorter induction-to-abortion time (11).…”
Section: Discussionsupporting
confidence: 59%
“…The median age of the women was 28 years . The women's body mass index (BMI) median was 23 kg/m 2 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Seven (7.8%) women were obese (BMI >30 kg/m 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Misoprostol 400 µg vaginally at 6-h intervals was considered to be the preferred regime in WA. All studies noted an increased incidence of side effects with increased misoprostol dosage; the main side effects were gastrointestinal, in particular vomiting [25][26][27][28]. There was a significant incidence of retained placenta following misoprostol abortion, as was the case with gemeprost-induced abortion, and this is also the clinical experience following spontaneous secondtrimester miscarriage.…”
Section: Medical Abortion In the Second And Third Trimesters: Gemeprostmentioning
confidence: 84%
“…Second-and third-trimester abortion in Australia over the past two decades has largely been medical rather than surgical; dilatation and extraction and hysterotomy are relatively uncommon. Several large studies and reviews have confirmed the efficacy of misoprostol for late abortion, including a study of 199 women in SA and another of 219 women from WA [25][26][27][28]. Misoprostol 400 µg vaginally at 6-h intervals was considered to be the preferred regime in WA.…”
Section: Medical Abortion In the Second And Third Trimesters: Gemeprostmentioning
confidence: 90%
See 1 more Smart Citation